Vibrational-state dependent decay dynamics of 2-pyridone excited to the S1 electronic state. Issue 37 (15th September 2022) - Yang, Dongyuan; Min, Yanjun; Feng, Baihui; Yang, Xueming; Wu, Guorong
Abstract : Vibrational-state dependent decay dynamics of 2-pyridone excited to the S1 electronic state is revealed by a time-resolved photoelectron spectroscopy study. Abstract : The S1 ( 1 ππ*) state decay dynamics of 2-pyridone excited around the 000 band origin is investigated using femtosecond time-resolved photoelectron imaging technique. At a pump wavelength of 334.0 nm, the vibrational ground state and a few low energy vibrational states covered by the bandwidth of the pump laser pulses are excited. The lifetimes of the vibrational states show strong dependence on the vibrational energy and mode. A quantum beat between two lowest energy vibrational states is also observed. This study provides quantitative information about the vibrational-state dependent lifetime of the S1 state of 2-pyridone.